(3eSFhdjI GdEOGQI Yf CYeGdgG GdJYGbOjI aj GdbGfhf GdeUQj hGdbGfhf GdYQGbj (B/s - (3EHQGgje NhQTjO eMeO GdeaQLjs; (3LGHQ LGO fUGQs; (3LGeYI GdOhd GdYQHjIs (3eYgO GdHMhK hGdOQGSGJ GdYQHjIs ((3GdbGgQI(B:s (3eYgO GdHMhK hGdOQGSGJ GdYQHjI(B- (3LGeYI GdOhd GdYQHjI,s, 2010)
(3ef GdeYQha Gdjhe Gf GdOhdI de JYO OhdI MGQSI abW habG ddeaGgje GdJbdjOjI Hd CVMJ Gdjhe OhdI eTGQcI dG JJQc eLGdkG Ch fTGWG EdG hWCJ bOegGEjGg ShGA HGdJfXje Ch HGdJbjO Ch HGdQNUI Ch HGdCPf ai eeGQSI gPG GdfTGW Ch Pdcs
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdOhd GdYQHjI, eYgO GdHMhK hGdOQGSGJ GdYQHjI, bSe GdbGfhf GdOQGSGJ GdbGfhfjI (B2010s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 178- 191(3UaMIs
Keywords: (3GdbGfhf GdEOGQjs; (3GdYbO GdEOGQj s; (3GdeSFhdjI GdJYGbOjI ddEOGQIs; (3bhGYO GdGNJUGUs; (3GdJYOjdGJ GdJYGbOjIs; (3OYGhi GdeSFhdjI GdJYGbOjIs; (3QSGFd LGeYjIs -- (3LGeYI GdOhd GdYQHjIs